Whole Earth Security A Geopolitics of Peace. Worldwatch Paper 55 - Deudney, Daniel; Worldwatch Inst., Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1983)
The current use and potential of technology for achieving security and peace are explored. Section 1 traces the use of technology for warfare through the mastery of ocean-going sailing, the maturation of the airplane, and the development of nuclear weapons. This section suggests that these developments have led to a loss rather than an increase in security. Section 2 discusses the "transparency revolution," which refers to the military reconnaissance, sensing, command, and communication systems literally wiring the earth with a web of electronic intelligence. Section 3 focuses on current military strategies: mutually assured destruction (MAD), nuclear utilization theories (NUTS), and, according to the author's personal projection, destruction-entrusted automatic devices (DEAD). The differences in these strategies are explained: to start a war in the MAD era would have required a major political misjudgment; in NUTS, a major human error; in DEAD, a major machine malfunction. Section 4 outlines elements of planetary security. It suggests that the same transparent technology now pushing superpower military competition to its most dangerous level can be used to construct an alternative security system. Section 5 promotes good neighbor politics. The final section concludes with the notion that while technology may have overwhelmed human ethical capabilities, it has not overwhelmed our passion for security. (KC)
Availability: Worldwatch Institute, 1776 Massachusetts Avenue, N.W., Washington, DC 20036 ($2.00).
ERIC Note: Financial support for this paper was provided by the Gund Foundation.
Microfiche.
Keywords: Global Approach; Modern History; Nuclear Warfare; Peace; Political Issues; Security (Psychology); Technological Advancement; World Problems; Interdependence; Opinion Papers